Strategi Komunikasi Dan Birokrasi: Satu Tinjauan Sejarah Aplikasi Amalan Perhubungan Awam Dalam Agensi Kerajaan Negeri Sabah - Syahruddin Ag Ahmad (Penerbit UM, 2008)
The practice of public relations complements tactics of organizational communication in terms of creating and disseminating messages within organization. Tactical message dissemination is technically used to get information direct from its sources as it will help management of the organization to make a crisp and accurate decision. Public relations task on tactical message dissemination are specially assigned to a particular person in this field purposely to gain image of his or her bosses as well as to enhance writing skills and surely to let everybody knows anything in an organization. A kind of job is successfully being traced back to 1959. Through the Press Officer and Junior Information Officer (Div. III, North Borneo Civil Service). As post-independent era in Sabah taking place the responsibility of these two position were also being took by Press Secretary. This study is organized by using content analysis technique to verify a bureaucratic elements those are implicitly practiced in such a job.